Real-Time 3D Interventional Echocardiography - Faletra, Francesco Fulvio; Perk, Gila.; Pandian, Natesa G.; Nesser, Hans-Joachim.; Kronzon, Itzhak; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
This book describes the use of real-time three-dimensional transesophageal echocardiography (3D TEE) in percutaneous interventional procedures, underlining its growing role and acceptance among interventional cardiologists, while also considering technique-related weaknesses. One issue has always been to provide trainees with appropriate learning tools and this reference will provide important support for those cardiologists taking their first steps in 3D TEE. Real-Time 3D Interventional Echocardiography includes information that all involved in the management of cardiac patients will find useful in terms of describing the anatomy of the structure to be treated (atrial septum, mitral valve), describing the morphopathology as seen with real-time 3D TEE (degenerative or ischemic mitral regurgitation), presenting up-to-date indications for the specific percutaneous treatment and, finally, providing descriptions of the procedures. Because interventional cardiology today ranges from closure of atrial and ventricular septal defects to repair of mitral regurgitation and aortic stenosis, from the closure of left atrial appendage and prosthesis dehiscence to the recent use of electrophysiological procedures, this book will be essential not only for specialists in echocardiography and interventional cardiology but also general cardiologists.
Technological Issues -- Closure of Patent Foramen Ovalis and Atrial Septal Defect -- Catheter-Based Repair of Mitral Valve Insufficiency -- Percutaneous Balloon Mitral Commissurotomy -- Transcatheter Aortic Valve Implantation -- Percutaneous Closure of the Left Atrial Appendage -- Closure of Post-AMI Ventricular Septal Defect -- Percutaneous Closure of Paravalvular Leaks -- The Role of 3D TEE in Ablation Procedures -- Miscellaneous Procedures.
Keywords: Medicine; Interventional radiology; Cardiology; Heart -- Surgery; Medicine & Public Health; Cardiology; Interventional Radiology; Cardiac Surgery